Impacts of Light and Food Availability on Early Development of Cassiopea Medusae - Muffett, Kaden McKenzie; Aulgur, Joleen; Miglietta, Maria Pia (Frontiers in Marine Science, 2022)
The Cassiopea genus is an emergent focus for behavioral, ecological, and genetic research. Cassiopea ephyrae, a key intermediate in the life cycle of this benthic jellyfish, have been left out of much work on the genus. Here we investigate the Cassiopea xamachana ephyra response to six combinations of light and feeding regimes. We show that zero light condition results in fast bleaching of ephyrae and significant reductions in bell size and predation success. We also show that ephyrae starved in sub-compensation level light experienced only meager reductions in size over 42 days, and those starved in zero light were still largely recoverable at 28 days. Developmental trajectories on various metrics of Cassiopea xamachana ephyrae were significantly impacted by both light and feeding level in the first 42 days of life.